Development of articulate storyline 3 based interactive media to support algebra learning - Zahra, Fatimah; Reflina (Desimal: Jurnal Matematika, 2025)
This research is development research (Research and Development) with the aim of developing interactive learning media based on Articulate Storyline 3 on algebraic material for students in grade VII SMP/MTs to determine its feasibility and practicality. The development model used is the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate. The results showed that the developed media obtained very high feasibility scores from material experts (87.5 percent) and media experts (89.3 percent). This indicates that the content is appropriate and the design supports effective learning. Furthermore, the practicality aspect was validated by responses from educators (94.2 percent) and students (89.4 percent), demonstrating that the media was easy to use, engaging, and supportive of classroom learning. These results suggest that the media not only meet academic standards but also resonate well with their users. Therefore, it can be concluded that the Articulate Storyline 3-based interactive learning media is both feasible and practical to be implemented in the teaching of algebra at the junior high school/MTs level. It is capable of helping students understand abstract mathematical concepts in a more interactive and enjoyable way, which may increase motivation and learning outcomes.